PENGARUH MODEL PEMBELAJARAN PAIKEM MENGGUNAKAN JARIMATIKA TERHADAP KEMAMPUAN BERHITUNG SISWA DI KELAS I SD NEGERI 03 TANJUNG BATU - Amallia, Indah; Allen Marga Retta; Puji Ayurachmawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2023)
This study aims to see and determine the effect of the PAIKEM learning model using jarimatics on the numeracy ability of students in grade I SD Negeri 03 Tanjung Batu. This research is a quantitative research using experimental methods with the type of Quasi Experimental Design. The variables of this study consist of independent variables, namely the PAIKEM learning model using mathematics (X) and dependent variables, namely students' numeracy ability (Y). The study population was all students of grades I - VI SD Negeri 03 Tanjung Batu which amounted to 376 students and the number of samples was 41 students. Data collection techniques using tests and documentation. Instruments to measure counting ability using pretest and posttest in the form of fill-in-the-blank questions. The experimental class group obtained an average pretest score of 71, and posttest of 88.88 and the control class obtained an average pretest score of 68.14 and posttest of 75.24. The results of the t test with Sig 0.000 < 0.05 and the result of t count 4.038 > t table 2.023, it can be concluded that there is a significant influence of the PAIKEM learning model using jarimatics on the numeracy ability of students in grade I SD Negeri 03 Tanjung Batu.